Liver glutathione and glutathione reductase response of endotoxin-treated mice. - Brown, P L (1975)
The decrease in the level of liver glutathione (GSH) in endotoxin-treated mice was in part due to formation of glutathione disulfide (GSSG). An electron-generating system (EGS) had no effect when incubated with soluble liver extracts from normal controls but resulted in recovery of GSH amounting to 25% in endotoxin-treated animals. Incubation in the absence of the EGS caused a decline of 16% in the GSH in extracts from normal animals compared with a 50% decrease in endotoxin-treated animals. Exclusion of nicotinamide adenine dinucleotide phosphate (NADP) from the EGS resulted in a slight decline in the GSH of the extract from the normal controls but 25% for the endotoxin-treated animals. Reduction of exogenous GSSG by the liver extracts required that exogenous NADP be added to ghe incubation mixtures.